2016
DOI: 10.1371/journal.pone.0159102
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and DNA Methylation Status of Glutathione S-Transferase Mu1 and Mu5 in Urothelial Carcinoma

Abstract: Bladder cancer is highly recurrent after therapy, which has an enormous impact on the health and financial condition of the patient. It is worth developing diagnostic tools for bladder cancer. In our previous study, we found that the bladder carcinogen BBN increased urothelial global DNA CpG methylation and decreased GSTM1 protein expression in mice. Here, the correlation of BBN-decreased GSTM1 and GSTM gene CpG methylation status was analyzed in mice bladders. BBN treatment decreased the protein and mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…It is known that BBN changes the protein expression of GSTM1, GSTO1 and NQO1 in the mouse urothelium after a 20-week treatment [ 22 , 35 ]. In this study, BBN also changed their expression, but arsenic did not alter this effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that BBN changes the protein expression of GSTM1, GSTO1 and NQO1 in the mouse urothelium after a 20-week treatment [ 22 , 35 ]. In this study, BBN also changed their expression, but arsenic did not alter this effect.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, BBN also changed their expression, but arsenic did not alter this effect. GSTM1, an antioxidant enzyme related to bladder cancer development [ 36 ], is down-regulated in protein and mRNA levels by BBN that are partially mediated by DNA methylation [ 35 ]. The decrease in GSTM1 may be involved in BBN-induced bladder carcinogenesis, but not directly related to arsenic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Previous study confirmed three primary genetic alterations which were consistently affect pathogenesis of papillary precursor lesion and non-muscle invasive bladder cancer (NMI-BC) including tyrosine kinase receptor fibroblast growth factor receptor 3 (FGFR-3), phosphatidylinositol-4, 5-bisphosphate 3-kinase, catalytic subunit α (PIK3CA) and Harvey rat sarcoma viral oncogene homolog (H-RAS). 45,46 In the other hand, alteration in tumor suppressor genes such as p16, Rb99 TP53 was oncogenesis machinery for the development of precursor neoplastic of muscle invasive bladder cancer (MI-BC) termed as CIS and urothelial dysplasia. Evidence also showed that the progression from papillary NMI-BC into high grade MI-BC was depend on TP53 and Rb activation.…”
Section: B Correlation Of Cigarette Smoke Exposure Dysplasia and Pmentioning
confidence: 99%
“…Some mechanisms of carcinogenesis in the urinary tract have been suggested. For example, DNA methylation retains cell proliferation in the normal urothelium [ 63 , 64 , 65 , 66 ]. One group of gene clusters was estimated taking into account the important role of miRNAs.…”
Section: Correlation Among Smoking Cancer and Expression Of Mirnmentioning
confidence: 99%